Cold agglutinin disease and its implications for dental treatment. (23rd May 2019) - Cho, Hana; Kumar, Navdeep
Abstract: Cold agglutinin disease (CAD) is a rare variant of autoimmune hemolytic anemia, characterized by the destruction of red blood cells by autoantibodies following exposure to cold temperatures. This case is of a 75‐year‐old male who presented to a dedicated hematology dental clinic. The dental management over a 3‐year period is described, whereby the patient had extraction and periodontal disease management with considerations for medical, social and dental risk assessments and treatment modifications. The principles are applicable to patients with other hematological disorders.